Dental anxiety – the importance of its management in dental appointments and the influence on children's oral health - Montagna, Diana (2022)
Introduction: The management of dental anxiety in children during a dental appointment is essential to the further success of dental treatments and to reduce the negative impact on child’s oral condition. Objectives: Assess levels of anxiety expressed by children during dental treatments and the degree of pain described in the same clinical context, in order to relate them with previous experiences and other etiologic factors. Methods: A cross-sectional study was conducted in a sample of 59 children from 8 to 14 years, who attended the Pediatric Dentistry appointments at the Dental Clinic of the Portuguese Catholic University in Viseu, Portugal. Data collection was accomplished by applying a questionnaire with questions about socio-demographic and oral health variables and also included two self-reported scales to measure anxiety and pain: Faces Version of the Modi ed Child Dental Anxiety Scale and Wong-Baker Faces Pain Scale. The decayed, missing and lled teeth index for permanent and deciduous teeth (DMFT and dmft index) was assessed. Results: Overall, 76% of the sample showed slight anxiety. Children between 8 and 11 years have a higher level of anxiety compared to those aged over 12 years. It was shown the impact of previous negative experiences in subsequent appointments (p < 0.001), in addition to increased susceptibility to pain (p < 0.01). The injection of local anesthesia has been shown responsible for 90% of anxiety and pain symptoms in children. Regarding oral condition, there was no relation between anxiety and the DMFT and dmft indexes. Conclusions: Anxious and uncooperative behaviour in the pediatric dental appointments occur in early ages. Additionally, the more invasive dental procedures are associated with higher expression of anxiety and pain.